(untitled) (Revista de Ciências Agroveterinárias, 2018)
Obesity is a disease characterized by excessive accumulation of body fat. It is caused by multiple factors, which can lead to the development of various secondary diseases such as heart disease and in the lower urinary tract, dermatopathies, diabetes mellitus and liver lipidosis. The aim of this study was to evaluate the biochemical serum profile of obese domestic cats. For this purpose, 21 domestic cats, of both sexes, with no defined breed, aged between 10 months and 14 years, were chosen according to the body condition score. Clinical and metabolic evaluations were performed in these animals. It was noted that 85.71% of the animals were castrated, and 52.38% of the animals had sedentary habits. For 71.43% of the males and 100% of the females were fed diets exclusive of feed and 42.86% of the cats were fed ad libitum. The mean values found showed urea and creatinine above the reference values, in which males presented higher values. AST and ALT also showed values above the normal values for the species. The values of total cholesterol, total proteins and fractions (albumin and globulins), glucose and alkaline phosphatase, when the minimum and maximum values were observed, showed non-normal results for the species. It is concluded that obesity can alter the biochemical serum values of the cats demonstrating increase in the value of urea, creatinine, AST and ALT.